Ultralight and spongy La–Mn-based perovskite catalysts modified by alkali metals and Ce: facile synthesis and excellent catalytic performance for soot combustion. Issue 4 (19th January 2023) - Yu, Xuehua; Yu, Di; Wang, Lanyi; Ren, Yu; Chen, Maozhong; Fan, Xiaoqiang; Zhao, Zhen; Sojka, Zbigniew; Kotarba, Andrzej; Wei, Yuechang; Liu, Jian
Abstract : Soot particles released from diesel engines have been considered as one of the main sources of air pollution, and the elimination of soot particles has become a crucial issue for air purification. Abstract : Soot particles released from diesel engines have been considered as one of the main sources of air pollution, and the elimination of soot particles has become a crucial issue for air purification. In this work, a series of La–Mn-based perovskite catalysts with hierarchical pores on the surface, where La ions were partially replaced with different alkali and Ce ions, were purposefully designed and successfully prepared by a facile method. In the prepared La–Mn-based perovskite catalysts, abundant ultramacropores, macropores and mesopores are simultaneously present on the surface, giving rise to their ultralight properties. The catalysts show high catalytic activity and stability in soot combustion, and the La0.8 Ce0.1 Cs0.1 MnO3 catalyst exhibited the best performance, with T 10, T 50 and T 90 of 268, 315 and 350 °C, respectively. Such catalytic activity is similar to or even higher than that of reported noble metal catalysts in the medium- and high-temperature range. The observed good catalytic performance was attributed to high contact efficiency between soot, reaction gases and catalysts provided by the developed pore structure and good redox properties of La–Mn-based perovskite catalysts promoted by the effect of alkali and Ce ions. In addition, the catalysts exhibit high sulfur and water tolerance. The possible reaction mechanism for soot combustion is also proposed based on the characterization, in situ DRIFTS studies and the determined TOF values. Owing to the facile synthesis, low cost, high catalytic activity and stability, the developed La–Mn-based perovskite catalysts exhibit a promising application potential in the elimination of diesel soot particles.